Characterization of Bacteria Associated with Pinewood Nematode Bursaphelenchus xylophilus - Vicente, Cláudia (2012)
Pine wilt disease (PWD) is a complex disease integrating three major agents: the pathogenic agent, the pinewood nematode Bursaphelenchus xylophilus; the insect-vector Monochamus spp.; and the host pine tree, Pinus sp. Since the early 80's, the notion that another pathogenic agent, namely bacteria, may play a role in PWD has been gaining traction, however the role of bacteria in PWD is still unknown. The present work supports the possibility that some B. xylophilus-associated bacteria may play a significant role in the development of this disease. This is inferred as a consequence of: (i) the phenotypic characterization of a collection of 35 isolates of B. xylophilus-associated bacteria, in different tests broadly used to test plant pathogenic and plant growth promoting bacteria, and (ii) greenhouse experiments that infer the pathogenicity of these bacteria in maritime pine, Pinus pinaster. The results illustrate the presence of a heterogeneous microbial community associated with B. xylophilus and the traits exhibited by at least, some of these bacteria, appear to be related to PWD symptoms. The inoculation of four specific B. xylophilus-associated bacteria isolates in P. pinaster seedlings resulted in the development of some PWD symptoms suggesting that these bacteria likely play an active role with B. xylophilus in PWD.